Small and Medium Enterprise Management Training to Increase Local Economic Productivity in Kadungora Garut - Kemala, Ratu; Nurdiana, Anne; Hermayanti, Yepa Sri; Maulida, Sifa (Pasundan Community Service Development, 2023)
Management training activities for Small and Medium Enterprises (SMEs) in Kadungora, Garut, West Java, are an important initiative in accelerating local economic growth through strengthening business management capacity. This training is designed to overcome the challenges faced by SMEs, including limitations in management, marketing and access to capital. With a significant SME population in Kadungora, this training is a catalyst for increasing productivity and local economic independence. The main objective of this training program is to improve participants' managerial abilities, optimize marketing strategies, and strengthen access to financing sources. Through a series of workshops, seminars, case studies, as well as mentoring and consultation sessions, this training offers practical and applicable insights. The resource persons involved are practitioners and experts in their fields, providing a holistic and integrated approach. The expected impact of this training includes increasing operational efficiency, local economic growth, and increasing the independence of business actors. Thus, this program not only contributes to improving the performance of SMEs in Kadungora but also encourages sustainable and inclusive regional economic growth. In conclusion, management training for SMEs in Kadungora is a strategic step in encouraging local economic prosperity. By combining theory and practice, this program prepares SMEs to face dynamic market challenges, while taking advantage of existing opportunities for the growth and development of their businesses.